The Role of Trust in Mediating the Effect of Digital Service Quality on Taxpayers’ Decisions at the Lubuk Pakam Tax Office Lubuk Pakam - Ahmad Fauzi Lubis, Dhani; Muharram Ritonga, Husni; Desy Surya, Elfitra (International Conference Epicentrum of Economic Global Framework, 2026)
This study aims to analyze the effect of digital service quality on taxpayers’ decisions, with trust as an intervening variable, among taxpayers at the Lubuk Pakam Primary Tax Office. This study employs a quantitative approach using a survey method. The sample consisted of 362 respondents, selected using probability sampling based on the Slovin formula. Data were collected via a questionnaire using a Likert scale and analyzed using Partial Least Squares-based Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS 3.0. The results indicate that digital service quality has a positive and significant effect on taxpayers’ decisions. Digital service quality also has a positive and significant effect on taxpayers’ trust. Furthermore, trust has a positive and significant effect on taxpayer decisions. The results of the indirect effect test indicate that trust significantly mediates the effect of digital service quality on taxpayer decisions. The coefficient of determination indicates that digital service quality explains 16 percent of the variance in the trust variable, while taxpayer decisions are explained by digital service quality and trust to the extent of 49.2 percent. These findings indicate that improvements in the quality of digital services not only have a direct impact on taxpayers’ decisions but also work through increased taxpayer trust. Thus, trust plays a crucial role in strengthening the relationship between the quality of digital services and taxpayers’ decisions at the Lubuk Pakam Primary Tax Office.